Upper airways in aspirin-exacerbated respiratory disease. Issue 1 (February 2015) - Choi, Jeong-Hee; Kim, Ji-Hye; Park, Hae-Sim
Abstract : Purpose of review: This review updates the status of chronic rhinosinusitis with nasal polyps (CRSwNP) in aspirin-exacerbated respiratory disease (AERD) in the contexts of epidemiology, diagnosis, pathogenesis, and treatment. Recent findings: Recent studies have shown that prostaglandin E2 (PGE2 ) deficiency induces an AERD phenotype in PGE2 synthase-1 knock-out mice and also PGE2 resistance in granulocytes of AERD patients. The numbers of platelet-adherent leukocytes increase in AERD patients, enhancing production of cysteinyl leukotrienes (CysLTs) via transcellular metabolism of arachidonate. INF-γ released from eosinophils of the sinus tissue of AERD patients promotes eosinophil maturation, increases leukotriene-associated gene expression, and releases CysLTs. The serum periostin level has been suggested to be a useful biomarker predicting the AERD/CRSwNP phenotype. Aspirin desensitization was reported to decrease the levels of CD4 + T cell-derived cytokines, including INF-γ and IL-10, in line with the newly defined role of INF-γ in AERD. Summary: Recent findings further support the notion that arachidonic acid metabolism is dysregulated in AERD patients. This is reflected by resistance to PGE2, overproduction of CysLTs by enhanced numbers of platelet-adherent leukocytes, and cellular stimulation by INF-γ released from eosinophils. Aspirin desensitization may be a useful treatment option in AERD patients exhibiting recalcitrant CRSwNP.